Spontaneous Postpartum Subacute Subdural Hematoma: A Case Report of Probable Compilation of Eclampsia - Gautam, Sachidanand; Meena, Shyam C; Gautam, Bhawana (Nepal Journal of Neuroscience, 2016)
The author presents a patient who developed a subacute subdural hematoma approximately 2 weeks after normal delivery with history of postnatal convulsion and lateralizing neurological symptoms. On day 12, she started to feel a nonpostural and severe throbbing headache with motor aphasia and right hemiparesis power grade 4, she was referred to our department. Left subacute subdural hematoma was confirmed by a computed tomography scan. Physical examination revealed only mild right hemiparesis. Left burr hole trepanation was performed and this was followed by uneventful postoperative course, and it completely recovered after 4 weeks. Chronic subdural hematoma should be considered when postpartum patients who have history of ecclampsia with mild to severe, persistent, and non-postural headache. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 109-111